Characterization of cracks on ultra thin continuously reinforced concrete pavements - Gerber, Johan Andries Kritzinger (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2011.